Elite haplotype of STRONG1 enhances rice yield by improving lodging resistance, panicle and plant architecture - Yong Zhao; Jie Gao; Xiaohong Wang; Muhammad Abdul Rehman Rashid; Zewen Wu; Zhiqi Ma; Hui Wu; Bingxia Xu; Zhenyuan Wu; Yunsong Gu; Yinghua Pan; Danting Li; et al. (Nature Communications)
Abstract Culm diameter directly affects lodging and yield traits in cereal crops. However, the underlying molecular mechanisms of these interrelated, complex agronomic traits remain unclear. Here, we identify a quantitative trait locus for culm diameter in rice (Oryza sativa) and cloned the candidate gene, STRONG1. This gene encodes MICROTUBULE-ASSOCIATED PROTEIN 70 (MAP70), which localizes to cortical microtubules and alters the arrangement of the microtubule skeleton. Knockout or knockdown of STRONG1 enhances grain yield by synchronously improving lodging resistance, panicle architecture, and plant architecture. One single-nucleotide polymorphism, SNP − 1304 (C to A), in a MYB61-binding site within the STRONG1 promoter affects its expression, resulting in changes in cellulose content and sclerenchyma cell wall development. Rice accessions harboring the Hap-STRONG1 C haplotype derived from wild rice, with reduced STRONG1 expression, show enhanced lodging resistance and yield, compared to accessions carrying Hap-STRONG1 A. Knockout of STRONG1 results in a 9.3–15.4% increase in yield, compared to the wild type in a field plot trial. Knockout of STRONG1 also improves panicle and plant architecture, facilitating high-density planting. This study provides a candidate gene for the development of improved rice varieties with stable, high yields.